1980
DOI: 10.1111/1523-1747.ep12531153
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Promotion by Abrasion Induced Epidermal Hyperplasia in the Skin of Mice

Abstract: Regenerative epidermal hyperplasia produced by repeated abrasion every 21 days of the skin of female mice after initiation with 7, 12-dimethylbenz(a)anthracene results in the appearance of epidermal tumors. Full thickness wounds, approximately 2 cm in length, made every 14 days in mouse skin initiated with 7, 12-dimethylbenz(a)anthracene also results in the appearance of epidermal tumors adjacent to the wound edge. Repeated abrasion or wounding of normal female mouse skin does not result in the appearance of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 8 publications
2
35
0
Order By: Relevance
“…In line with this, whilst the above changes brought about by TPA are also brought about by certain kinds of epidermal injury such as wounding and full thickness abrasion which are also promoting stimuli (Hennings & Boutwell, 1970;Clark-Lewis & Murray, 1978;Argyris, 1980a) they are also produced by non-promoting stimuli such as mild abrasion by sandpaper rubbing (Marks et al, 1979) and treatment of the skin with the calcium ionophore, A23187 (Marks et al, 1981;KleinSzanto et al, 1982). Similarly, with the exception of dark cell induction (Klein-Szanto et al, 1980 all the TPA-induced effects cited above are produced with at least equal potency by the second stage promoters mezerein (Mufson et al, 1979) and RPA (Furstenberger et al, 1981).…”
Section: Two-stage Epidermal Tumourigenesismentioning
confidence: 84%
See 3 more Smart Citations
“…In line with this, whilst the above changes brought about by TPA are also brought about by certain kinds of epidermal injury such as wounding and full thickness abrasion which are also promoting stimuli (Hennings & Boutwell, 1970;Clark-Lewis & Murray, 1978;Argyris, 1980a) they are also produced by non-promoting stimuli such as mild abrasion by sandpaper rubbing (Marks et al, 1979) and treatment of the skin with the calcium ionophore, A23187 (Marks et al, 1981;KleinSzanto et al, 1982). Similarly, with the exception of dark cell induction (Klein-Szanto et al, 1980 all the TPA-induced effects cited above are produced with at least equal potency by the second stage promoters mezerein (Mufson et al, 1979) and RPA (Furstenberger et al, 1981).…”
Section: Two-stage Epidermal Tumourigenesismentioning
confidence: 84%
“…Why for example, does wounding (Hennings & Boutwell, 1970;Clark-Lewis & Murray, 1978) or deep abrasion (Argyris, 1980a) promote tumours whereas milder forms of epidermal manipulation (Clark-Lewis & Murray, 1978;Marks et al, 1979) do not. Marks et al (1982) have introduced the concept that a 'woundspecific' response is crucial to tumour promotion by injury and by TPA and have suggested that the release of a 'wound-hormone' may be critical in the former instance.…”
Section: Two-stage Epidermal Tumourigenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Sci. USA 90 (1993) ogen-treated mice but not in untreated mice (21)(22)(23). Of special interest is the fact that those tumors developed close to the wound edge.…”
mentioning
confidence: 99%